(untitled) (Theatrum historiae, 2010)
The author of this study follows the fate of the aristocrat Vok the Fifth of Holštejn, which is corroborated by written records dating back to between 1420 and 1466. The aim of the work is to show how it was possible to fall into the bankruptcy trap in the first half of the 15th century. While Vok’s father of the same name had relatively extensive property in Moravia, Vok the Fifth lost practically all of it during his lifetime. His entire life was dogged by permanent, endless debts. The author comes up with the likely hypothesis that the bankruptcy of Vok the Fifth of Holštejn was caused by the Hussite Wars, or rather the debts he accumulated during the course of these wars. If this theory is correct, it would make Vok the Fifth one example of a noble who, instead of getting rich through Hussitism, was financially ruined.